Comprehensive Review of Tube Feeding in Clinical Practice: Indications, Methods, Complications, and Innovations (Journal of Advances and Scholarly Researches in Allied Education, 2025)
When patients with fully functioning gastrointestinal tracts are unable to satisfy their nutritional requirements orally, tube feeding, also known as enteral nutrition (EN), becomes an essential intervention. The indications, kinds of tubes, insertion procedures, formula choices, problems, monitoring protocols, ethics, and new technology related to tube feeding are all thoroughly covered in this study. To aid in clinical decision-making, suggestions based on evidence are provided with comparison tables.